Wednesday

April 23, 2014

April 23, 2014

Posted by **Pam** on Tuesday, August 2, 2011 at 7:33pm.

8x+6=2x+9

8x-2x+6=2x-2x+9

6x+6=9

6x+6-6=9-6

6x=3

6/2= 3/6=1/2

x=1/2

- Math -
**Ms. Sue**, Tuesday, August 2, 2011 at 7:37pmYay! You've got it.

I think this line >>

6/2= 3/6=1/2

should be

6x/6 = 3/6

x = 1/2

- Math -
**Kris**, Tuesday, August 2, 2011 at 7:44pmThanks!

- Math -
**Ms. Sue**, Tuesday, August 2, 2011 at 7:47pmYou're welcome.

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Math - Can someone please check my answers below for accurateness? The ...

math correction - Directions: Perform the indicated divisions. The problem: (8x^...

Business Calculus - The indefinite integral, or which call the "antiderivative...

principles of math 11 - if f(x)=2x =1 and g( x) =4x-3 then (f+g)(x)= options are...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

math-calculus - 4x+3/2x-1-2 = 6x+2/2x-1 (4x+3)(-2) = (6x+2) -8x-6 = 6x+2 -14x-6...

Math - The expression (3x+4) (2x-6) is equavalent to? 3x(2x-6)+4(2x-6) multipy ...

math 012 - not so sure about this one either. (anything typed such as 7/6 are ...

math-calculus - i think i do something wrong again(2x+1)/(x-3)-(4x-1)/(2x-3) = 0...